Ts 825 2.derece Gün Bölgesinde Yer Alan İllerin, Isıtma Ve Soğutma Derece Gün Bölgelerine Göre Değerlendirilmesi - Tanrıverdi, Baran (Enerji Enstitüsü, 2015)
Bina performansı değerlendirilmesinde konfor koşullarına göre enerji tüketiminin belirlenmesi önemli bir değişkendir. Enerji tasarrufu sağlanırken, iç ortam konforunun düşürülmemesi dikkat edilmesi gereken bir durumdur. Enerji tasarrufu sağlamak için bina kabuğunda kullanılan ısı yalıtım malzemeleri, kimi zaman binanın nefes alamamasına ve bazen de istenmeyen kabuk katmanında oluşan kontrolsüz yoğuşmalar nedeniyle küf ve bakteri oluşumuna neden olur. TS 825 standardı binalarda ısı yalıtım kuralları ve yıllık ısıtma enerjisi ihtiyacının optimize edilmesine yönelik bir standarttır. TS 825 Standardı binanaların enerji tüketimi ve nem transferi hesaplamalarını ısıtma derece gün bölgesine göre yapmaktadır. Standartta illere ait soğutma enerji tüketimi ve yaz şartlarında oluşacak yoğuşma özellikleri ile ilgili hesaplama yapılmıyor olması değerlendirilmesi gereken bir konudur. Ayrıca bina kabuğunda nem transferi ve yoğuşma konularının, aynı iklim bölgesinde yer alan iller için bile farklılık gösterebileceği göz önünde bulundurulmalıdır. Bu çalışmada aynı iklim bölgesinde bulunan illerde, soğutma enerji ihtiyacının önemi yapılan enerji performansı modellemesi yöntemleriyle ortaya koyulması hedeflenmiştir. Ayrıca güncel meteorolojik istasyon değerleri dikkate alınılarak, nem transferi konusunda soğutma sezonunda oluşabilen olumsuz durumlara vurgu yapmak hedeflenmiştir. Bu tez çalışmasında öncelikle, TS 825 standardına 2.derece gün iklim bölgesinde yer alan, birbirinnden farklı ısıtmave soğutma derece gün sayılarına sahip olarak seçilmiş dört illin, mevcut bir konut binası üzerinden enerji tüketiminin değerlendirilmesi yapılmıştır. Isıtma ve soğutma enerji tüketimlerinin etkinliği ortaya koyulmuştur. Sonrasında yine aynı standartta 2. derece gün bölgesi için bina kabuğu elemanlarından dış duvar ve çatı için tavsiye edilen ısıl geçirgenlik katsayısı değerlerine göre iyileştirilen binanın yeni durum için enerji performansı değerlendirilmesi yapılmıştır. Aydınlatma ve elektirkli ekipmanların enerji tüketimleri de değerlendirilerek toplam enerji tüketimleri mevcut ve iyileştirilmiş durumlar için karşılaştırılmıştır. Son olarak da mevcut ve standarda uygun olarak revize edilen binada nem geçişi ve yoğuşma özellikleri incelenmiştir. Bu bilgiler ışığında çıkan sonuçlar tartışılmış ve önerilerde bulunulmuştur. Enerji tüketiminin hesabında ASHRAE Transfer Fonksiyonu Metodunu kullanan HAP 4.8 enerji modellemesi yazılımı kullanılmıştır. Nem transferi ASHRAE temel el kitabında yer alan yönteme göre hesaplanmıştır.

Building energy consumpiton and energy efficiency issues become a key research subject related to increasing energy demand, depletion of the energy resources, incresing greenhouse gases and ozone layer depletion. In most countries leading USA and European countries started working on to decrease the energy demand. The building energy efficiency standarts and regulations revised according to these updated issues. In Turkey high percentage of energy demand is provide from fossil fuels. According to national energy and climate changes action plan, the usage of primary energy sources are 30.9% natural gas, 31% coal, 28.8% petroleum, 4.4% biogas, 2.9% hydro, 1.2% geothermal, 0.4% solar and, 1.2% wind energy. In building performance, analysing energy consumption considering thermal comfort is a key parameter. While working on energy efficiency, thermal comfort is anothter parameter that can not be dismissed. The insulation materials used in building envelope some times prevent the air diffusion of building and sometimes ensures undesired condensation in some layers of the envelope. This consists moisture and bacterial growth. TS 825 involves thermal insulation requirements and annual heating energy performance optimization for buildings. The standart first revelaed in 1999 for energy performance of buildings. The final revision is done in 2013. The method of the standart is grouping the cities according to heating degree days. All U values, outdoor design temperatures and base building heating load and energy consumpitions are standardised acording to these heating degree day zones. However standart does not include cooling issues. For cooling session, the standart neither includes cooling energy performance issues nor condensation issues. These are important issues for whole building simulations analysis. In TS 825, moisture transfer and condensation issues are evaluted in same way in the same degree day zones. This is another issue to pay attention carefully. Energy consumption analysis and moisture transfer issues are based on heating degree day calculations in TS 825 standart. Cities which have different climate conditions are evaluated in same degree day zone. The only parameter is the proximity of the heating degree days. Cooling energy conspumtion, thermal comfort and condensation calculations in summer contitions are the unadressed issues in the standart. This study targets the importance of cooling conspumtion and cooling energy efficiency in buildings. And also point out the moisture transfer and condensation issues in summer time. In the second chapter of the study building energy performance design parameters have been informed. BEP TR and its methodology are explained. In the third chapter of the study TS 825 degree day zones are explained. The division of the degree day zones are explained according to cities. The changing parameters according to degree day zones are informed. In the fourth chapter of the study energy modelling and parameters are explained. The input and output datas are introduced. And finally the calculation methodology of the simulation tool and formulas are explained. For the energy simulation in case study HAP 4.8 tool is used. HAP modelling tool is a ASHRAE Transfer Funciton based programme. Also uses ASHRAE energy modelling flow chart in calculation steps. ASHRAE moisture calculation is used for moisture transfer and condensation analysis. Moisture transfer is dependent on many indoor and outdoor parameters such as water vapour from internal equipments, water leakage, rain carried by wind, water leakage from foundation and vapour transfer through buinding materials. All these parameters calculated according to ASHRAE fundementals moisture calculations. In this study energy consuption performance of a typical residential building is examined for cities which are referenced in 2. degree day zone in TS 825. The typical residential building has same envelope, facade and internal load parameters in all cities. The outdoor temperature and relative humidity conditons differences are the main comparement to discuss. For energy consumption comparement, heating and cooling energy consumption performances are presented for all contitions. After that external wall and roof U-values were restored according to TS 825's recommendations about these components. According to these improvements cooling and heating energy consumption analysis is revised. In TS 825 standart moisture transfer and condensation analysis are calculated according to heating degree day zones. Same outdoor temperature values are used for all cities in same zone. When using mean temperature values, examining critical condensation points become difficult. Therefore extreme temperature values from meteoroligical stations are used to calculate moisture transfer. Although Istanbul, Rize, Diyarbakir and Muğla are in the same degree day zone according to TS 825, there are big differences about energy consumption and moisture transfer issues in these cities. The improvement in building envelope according to TS 825 standart provides large energy efficiency both in heating and cooling in all design cities. It is seen that energy saving in heating reaches up to 70% and energy saving in cooling reaches up to 30%. Energy consumption for cooling is as much as heating for buildings in hot climates. Cooling thermal comfort has become a must such as heating. Because of this energy consumption for cooling has to be examine carefully. In the other hand it is seen that moisture transfer and condensation issues are deeply concerned with internal temperature and relative humidty in summer and winter conditions. It is an significant issue even though it is insulated according to TS 825 standart. In Istanbul, Rize and Diyarbakir 1 ˚C change for internal design temperature causes to condensation. In these cities insulated wall pressure curves are in critical points even in insulated case.   In Istanbul and Rize, moisture transfer is an issue also to be analyised in cooling conditions. Insulation materials have high diffusion resitance properties sometimes blocks the moisture pass through walls. Therefore it can cause problems even in summer contitions which are not evaluated in TS 825 standart. It is also concluded that moisture transfer analysis is only a must for heating conditions in such cities like Diyarbakır and Muğla in which relative humidity is low in summer time. Recomendations about moisture transfer in TS 825 standart is enough for providing condensation. TS 825 standart is prepeared according to heating energy consumpiton and winter time moisture transfer. The improvements in standart about building envelope does not include issues about cooling energy consumption reduction and summer time moisture. These are the issues have to be considered for whole building design. The computer simulations which are ASHRAE Transfer Funciton Based HAP4.8 has been used for energy consumption. Moisture tansfer and condensation is calculated according to ASHRAE fundementals.
Comparison Of Heating And Cooling Degree Days Of States İn 2nd Degree Day İn Ts 825
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Enerji; Yapılar; Isı özellikleri; Energy; Buildings; Thermal properties